Pengabdian kepada Masyarakat Pembelajaran Berbasis STEM Bagi Guru - Guru Sekolah Dasar di Kabupaten Bandung - Sukmana, Rika Widya; Nurhayati, Yeti (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2019)
Training of Science, Technology, Engineering and Mathematics (STEM) approach, to improve professionalism for elementary school teachers at SDN Griya Bandung Indah (GBI), Bandung was conducted for community service. The target of the training is elementary school teachers in SDN Griya Bandung Indah (GBI), Bandung.. Problems are solved in three stages of activity, namely preparation, implementation and evaluation. Preparation is done by conducting a preliminary survey to see the conditions in the field regarding teachers’ professional development. Implementation is done by training, using lecture method that is with presentation technique, followed by practice of micro teaching about STEM. Evaluation of activities carried out for each stage by collecting and summarizing data from each stage of activity. The results of the training activities show the success rate with an indication of material conformity with the needs of SDN Griya Bandung Indah (GBI), Bandung teachers, positive responses from the participants, and most participants have understood the STEM approach.